2016
DOI: 10.3847/2041-8205/828/1/l9
|View full text |Cite
|
Sign up to set email alerts
|

A Microfilament-Eruption Mechanism for Solar Spicules

Abstract: Recent investigations indicate that solar coronal jets result from eruptions of small-scale chromospheric filaments, called minifilaments; that is, the jets are produced by scaled-down versions of typical-sized filament eruptions. We consider whether solar spicules might in turn be scaled-down versions of coronal jets, being driven by eruptions of microfilaments. Assuming a microfilament's size is about a spicule's width (∼300 km), the estimated occurrence number plotted against the estimated size of erupting … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 54 publications
2
19
0
Order By: Relevance
“…Our results support the hypothesis that fast spicules originate from magnetic reconnection (14,20,21). It is possible that a sub-photospheric local dynamo mechanism (22) or magnetoconvection process (13,23) generates weak magnetic fields close to the large-scale network fields.…”
supporting
confidence: 87%
“…Our results support the hypothesis that fast spicules originate from magnetic reconnection (14,20,21). It is possible that a sub-photospheric local dynamo mechanism (22) or magnetoconvection process (13,23) generates weak magnetic fields close to the large-scale network fields.…”
supporting
confidence: 87%
“…Later, this rebound shock model was improved by including radiation and heat conduction in the model (e.g., Sterling & Mariska 1990;Cheng 1992;Sterling et al 1993;Heggland et al 2007;Kuźma et al 2017). Recently, Sterling & Moore (2016) have reported that the microfilament-eruptions can be a potential candidate for the generation of spicules. Murawski & Zaqarashvili (2010) performed 2D numerical simulations with a velocity pulse to produce the spicule.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together with the results of Panesar et al [66][67][68] they also claim that flux cancellation is the main process whereby the energy is stored prior to eruption in all jets and CMEs, and may also be involved in the triggering process. So far, the finding of blowout jets has been confirmed by many observational studies, and now we recognized that the vast majority of solar jets are caused by magnetic flux cancellation rather than flux emergence [62,[69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84]. Recently, high resolution observational studies showed that two-sidedloop jets are also associated with flux cancellations and include the eruption of mini-filaments inside the base arches [43,46,49,85,86], and two-sided-loop jets occurring in filament channels may important for causing the eruption of large filaments [87].…”
Section: Observational Feature (A) Morphology and Classificationmentioning
confidence: 78%
“…Shen et al [62,69] studied two blowout jets and found that the erupting mini-filaments directly form the cool component of coronal jets (see Figure 2). Recently, more and more observational studies confirmed that blowout jets are driven by mini-filament eruptions or filament channels [73][74][75][76][77][78][79][80][81][82][83][84]97,98]; some authors even proposed that all coronal jets are originated from mini-filament eruptions, and their generation resembles the eruption of large-scale, energetic filament/CME eruptions [36,65,99].…”
Section: (B) Precursormentioning
confidence: 99%